Motivasi Dakwah Bilhal Melalui Seni Hadroh Di Jepang: Studi Kasus Hadroh Nusantara Tokyo Jepang - Fuad Hasan Baihaqi; Herma Musyanto; Ahmad Habibul Muiz (Hikmah, 2025)
This study aims to analyze the motivation for preaching through the art of hadroh within the Hadroh Nusantara Tokyo community as a form of cultural da'wah practiced by Muslim minorities living in Japan. In a context where Islam exists as a minority religion within a secular and pluralistic society, cultural approaches to da'wah become strategically important. This research employs a descriptive qualitative method, with data collected through in-depth interviews, participatory observation, and documentation of community activities. The theoretical framework integrates Self-Determination Theory, which emphasizes psychological dimensions of motivation such as autonomy, competence, and relatedness, with Islamic Motivation Theory, which highlights spiritual, social, and individual dimensions of human action grounded in faith.The findings indicate that members’ involvement in hadroh activities is driven by both intrinsic and extrinsic motivations. Intrinsically, participants perceive hadroh as a form of worship (ibadah), spiritual expression, and personal fulfillment. Extrinsically, hadroh serves as a medium for social interaction, cultural preservation, and collective identity formation among Indonesian Muslim migrants in Japan. Furthermore, the art of hadroh functions as a non-verbal communication tool that effectively transcends linguistic and cultural barriers, enabling the dissemination of Islamic values in a peaceful and inclusive manner. Through rhythmic music and devotional lyrics, hadroh contributes to strengthening community solidarity while simultaneously fostering a positive, moderate, and adaptive image of Islam within Japanese society. Overall, this study concludes that hadroh art is an effective and relevant medium of da'wah, reinforcing Islamic identity and spiritual resilience among Muslim diasporas while promoting intercultural harmony in a multicultural environment